Identification of runs of homozygosity associated with male fertility in Italian Brown Swiss cattle - Pacheco, Hendyel A.; Rossoni, Attilio; Cecchinato, Alessio; Peñagaricano, Francisco (Frontiers in Genetics, 2023)
Intensive selection for improved productivity has been accompanied by an increase in inbreeding rate and a reduction in genetic diversity. The increase in inbreeding tends to impact performance, especially fitness-related traits, such as male fertility. Inbreeding can be monitored using runs of homozygosity (ROH), defined as contiguous lengths of homozygous genotypes observed in an individual's chromosome. The goal of this study was to evaluate the presence of ROH in Italian Brown Swiss cattle and assess its association with bull fertility. First, we evaluated the association between ROH and male fertility using 1,102 Italian Brown Swiss bulls with sire conception rate records and 572k SNPs spanning the entire genome. Second, we split the entire population into 100 high-fertility and 100 low-fertility bulls to investigate the potential enrichment of ROH segments in the low-fertility group. Finally, we mapped the significant ROH regions to the bovine genome to identify candidate genes associated with sperm biology and male fertility. Notably, there was a negative association between bull fertility and the amount of homozygosity. Four different ROH regions located in chromosomes 6, 10, 11, and 24 were significantly overrepresented in low-fertility bulls (Fisher's exact test, P-value < 0.01).Remarkably, these four genomic regions harbor many genes, such as WDR19, RPL9, LIAS, UBE2K, DPF3, 5S-rRNA, 7SK, U6, and WDR7, that are related to sperm biology and male fertility. Overall, our findings suggest that inbreeding and increased homozygosity have a negative impact on male fertility in Italian Brown Swiss cattle. The quantification of ROH can contribute to minimizing the inbreeding rate and avoid its negative effect on fitness-related traits, such as male fertility.